Being and planning - Sturup, Sophie; Low, Nicholas (AESOP, 2015)
Hannah Arendt in The Human Condition wrote of the substitution, in modern times, of the ‘social’ for the ‘political’, thereby creating a situation of ‘worldlessness’ wherein the ground on which we could be held to account for our self-construction has disappeared. This ‘worldless’ world, in Peter Wagner’s words, is ‘a world in which social relations may have global extensions, but are so thin and ephemeral that contemporary modern human beings are held to realize their own lives in a social context that they cannot conceive as their own’ (Wagner 2012, 66). Planning is left trying to construct a collective reality in an ephemeral and indeterminate social context where the only ground for determinations of truth and right is individual opinion. In this paper we approach the question of ‘worldhood’ from the ontological and phenomenological perspective of Heidegger’s Being and Time. We attempt a preliminary exploration of the ‘Being’ of planning and the ‘Being’ of planner as Dasein (the one that is there, for whom the world occurs). Our task is to identify the ‘worldhood of the world’ of planning and planner, and relate Heidegger’s insights to the problem of ‘worldlessness’ facing the planner in today’s modernity. From Being and Time we take two aspects of Heidegger’s thought of helpful potential for planning in a worldless world, his concepts of authenticity and truth, noting that Heidegger always thinks in terms of both the positive and privative (or deficient) modes of qualities with which Dasein relates to Others and to the world.
Book of proceedings: Annual AESOP Congress, Definite Space – Fuzzy Responsibility, Prague, 13-16th July, 2015